2006 GEP-ISFG collaborative exercise on mtDNA: reflections about interpretation, artefacts, and DNA mixtures - Prieto, L.; Alonso, A.; Alves, C.; Crespillo, M.; Montesino, M.; Picornell, A.; Brehm, A.; Ramirez, J. L.; Whittle, M. R.; Anjos, Mt; Boschi, I.; Buj, J.; et al. (Elsevier B.V., 2008)
We report the results of the seventh edition of the GEP-ISFG mitochondrial DNA (mtDNA) collaborative exercise. The samples submitted to the participant laboratories were blood stains from a maternity case and Simulated forensic samples, including a case of mixture. The success rate for the blood stains was moderate (similar to 77%); even though four inexperienced laboratories concentrated about one-third of the total errors. A similar success was obtained for the analysis of mixed samples (78.8% for a hair-saliva mixture and 69.2% for a saliva-saliva Mixture). Two laboratories also dissected the haplotypes contributing to the saliva-saliva mixture. Most of the errors were due to reading problems and misinterpretation of electropherograms, demonstrating once more that the lack of a solid devised experimental approach is the main cause of error in mtDNA testing. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: mtDNA; Mixture; Recommendations; Phylogeny; GEP-ISFG; Collaborative exercise